Illyricum of the 2nd and 3rd centuries A.D. in the works of Latin and Greek historians - Gračanin, Hrvoje (2005)
The author anaylizes and evaluates the data in the works of several Greek and Roman historians ranging from the 3th to 5th centuries A.D. in regard to the history of Pannonia and Dalmatia in the 2nd and 3rd centuries A.D. The paper deals with the context and type of data, the manner in which they were presented, the special interest of the Greek and Roman historians shown for provinces of Pannonia and Dalmatia respectively, and the perception of the role of Illyricum in history of the Roman Empire. The data from the analyzed sources are mostly concerned with the military and political history of the Illyrian provinces. The barbarian incursions and attempts to check them and to stop the plunderings, the civil wars and struggles between the imperial pretenders are a predominant theme. The troubled situation in these provinces generated apparently interest even if more than a century had passed from certain events. Still, there is a noticeable difference in treatment of data, which is, of course, dependent on the genre of a specific historiographic work (the imperial biographies and the breviaria provide only shorter accounts), and on its completeness (Dio’ s work is preserved only fragmentarily, Zosimos’ first book is also lost partially, and it seems that the Historia Augusta did not come down to us in its integral form, too). Thus Dio deals with the Marcomannic wars of Marcus Aurelius in the 2nd century more or less detailed, Victor, Eutropius, Rufius Festus, the Epitome de Caesaribus and the Historia Augusta gave them some attention, but they were totally ignored by Zosimos. On the other hand, the 3rd century troubles were given a fair attention in the Historia Augusta, incidental in Eutropius, Victor, and the Epitome de Caesaribus, and even Zosimos provides a glimpse of them. The common feature of the analyzed sources is their awareness of Illyricum’ s exceptional importance, and the 4th century sources emphasize regularly the role of the Illyrian emperors in the defence and restoration of the Empire. One has to point out that the authors who spent a part of their lives in Illyricum do not show close familiarity with the western Illyrian region regarding the situation in the 2nd and 3rd centuries. Dio might be considered as an exception to it, because he states that he writes with exact knowledge of conditions in Pannonia, based on his own experience (49.36.4), which can be corroborated in a few cases. However, a specific interest can be detected with several authors (Herodian, Zosimos, Victor, the Anonymous of the Epitome de Caesaribus, Rufius Festus).
Projekt MZOS
ENG